Drug-Drug Interactions (DDIs) in Elderly Hypertensive Inpatients - Titami, Arina; Wiedyaningsih, Chairun; Pramantara, I Dewa Putu (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: The prevalence of hypertension is higher among the elderly population. Elderly patients are considered a high-risk population for Drug-Drug Interactions (DDIs) due to multi-morbidity-related polypharmacy, age-related physiological changes, as well as pharmacokinetic and pharmacodynamic changes.Objectives: This study conducted a drug use survey in the inpatient department of the Academic Hospital of Universitas Gadjah Mada Yogyakarta to assess Drug-drug interactions (DDIs) in individual prescriptions for elderly hypertensive patients.Methods: This research employs an observational study design with a retrospective cohort approach. This study was conducted at the Academic Hospital of Universitas Gadjah Mada Yogyakarta in January-December, 2021. The inclusion criteria for this study included patients diagnosed with hypertension, aged 60 years or older and those hospitalized. Ethical approval for this research was granted by the Faculty of Medicine, Public Health and Nursing Research Ethics Commission at Universitas Gadjah Mada, Yogyakarta under approval number KE-FK-0500-EC-2022.Results: 120 prescriptions from 120 patients were collected from the medical records maintained by the Academic Hospital of Universitas Gadjah Mada Yogyakarta. This study identified 66 cases of Drug-Drug Interactions (DDIs), mainly due to drug interactions comprising 8 interactions unrelated to hypertension, and 58 related to hypertension. Three actual drug interaction events resulted in increased blood pressure, while the others were potential drug interactions.Conclusion: From this study, it can be concluded that elderly patients are considered a natural high-risk population for DDIs. Each patient should be assessed individually based on their prescriptions, although in many cases, DDIs are unavoidable.Keywords: Drug-Drug Interactions; Elderly; Hypertension; Inpatients